Re- reading Nissim Ezekiel through the mirror of post colonialism. - Karmakar, Goutam (American Journal of Humanities and Social Sciences, 2015)
In the genre of Indian English Poetry, Nissim Ezekiel stands as a flagship, founder and father of post-independence period. And any discussion regarding the poetic journey and development of Indian English poetry will definitely start with Nissim Ezekiel. He did the same thing what Walt Whitman did for American poetry. He is classifies both as a modernist and post modernist poet. And this can be found in the first half of his poetry. But a close looks to some of his poetry shows that his poetry manifests or reflect the gesture of post colonialism. Now-a-days cultural studies and theory of post colonialism become a fashion and also Nissim Ezekiel can be re-read by applying these cultural studies and post colonial theory to some extent. He wants to confirm his identity and also wants to hark back the colonial past of India. Not only this, he also uses myth in his poetry. This paper attempts to highlight those issues and aspects in the poetry of Nissim Ezekiel where he tends towards post colonialism.